Narrativa, tempo e limites da linguagem - Marco Guisoli Girardi de Mendonca (2017)
This dissertation aims to carry out a theoretical reflection concerning two different discursive orders, history and psychoanalysis. The initial problem is related to some questions raised by the philosopher Paul Ricoeur, and can be formulated as an attempt to verify correspondences between the psychoanalytical concept of working-through (Durcharbeitung) and the historical narrative as conceived among Ricoeurs hermeneutic circle. As a result, three aspects that constitutes both disciplines can be brought to light, which are the precedence of past time; the linguistic effort to apprehend the real; and the capacity to (re)signify the action. Thus, under the impact of the debates carried out by Michel Certeau, the research moves on to investigate contributions that history can retain from the temporal dynamic of psychoanalysis. Once the latter is investigated, the study reaches its closing, in which a fourth characteristic stands out, and both history and psychoanalysis offer theoretical supports that illustrate the limits of the language in its apprehension of the real.